Students' perspectives on teacher expectations and mathematics achievement - Zhang, Ying; Ahmad, Nor Aniza (Faculty of Educational Studies, Universiti Putra Malaysia, 2016)
Educators are not just responsible for delivering academic knowledge but they also should be concerned about the students’ inner psychological state. Teacher transmits different kinds of expectation towards their students that it will differ in their behaviors. It is better for educators to pay attention to students’ views on teacher expectation as well as care about students’ mathematics achievement. Since both teacher’ expectation and behaviors are exterior factors for students, they have to be perceived before performing the functions on students. Students’ perception is the bridge that connects teachers’ expectation and students’ performance. Previous research demonstrates that students are sensitive to teachers of speech, attitude and body behaviors and could perceive teachers’ expectation implied by them (cooper &good, 1983). This paper gives an overview of the teacher expectation theory and its related model, teacher expectation effect, the extent of teacher expectation and teacher expectation and academic achievement. A wide range of literature are discussed and described in this research.